The Relationship Between Psychological Adaptation and Anxiety Level In The New Normal Era At Central Lombok - Purqoti, Dewi Nur Sukma; Rusiana, Harlina Putri; Oktaviana, Elisa; Ernawati, Ernawati; Rispawati, Baik Heni (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Covid-19 affects all aspects of life such us health, social, economy, education, politics and development that cause psychological distress and anxiety. The purpose of this study was to determine the relationship between psychological adaptation and community anxiety levels in the new normal era. This study uses analytic cross sectional design.The sampling technique in this study was simple Random Sampling of 54 respondents. Data analysis used the Chi Square test. The results: Obtained p value = 0.033, it can be concluded that there is a difference in the proportion of anxiety levels between mal-adaptive respondents with adaptive respondents, which means that there is a significant relationship between psychological adaptation and anxiety levels with OR=6,821